Mitigating Plagiarism in ESL Academic Writing: Evaluating the Efficacy of Educational Intervention - Nazirah Mahmud; Mohd Haniff Mohd Tahir (Journal of Language and Education, 2024)
Background: Plagiarism is a serious academic misconduct demanding mitigation to uphold the integrity of original work. Undeniably, with the advancement of technological age, plagiarising becomes easier and harder to detect. However, the reliance on technology significantly rises the likelihood of fostering academic dishonesty among the students. Therefore, it is imperative to disseminate explicit education on plagiarism reduction strategies, particularly on the importance of mastering correct referencing techniques.Purpose: The present study applied a mixed-method approach to explore the effectiveness of an intervention called Educational Intervention (EI) on enhancing ESL students’ academic referencing skills namely in in-text citation abilities, paraphrasing skills and writing reference list using APA style.Method: The EI consisted of explicit instruction that involved structured teaching sessions integrated with two primary instructional strategies: lectures and practical exercises on referencing in academic writing. A total of 70 participants participated in the study. Data collection involved administering tests, assigning exercises and assignments, and conducting focus group interviews. The study utilised a quasi-experimental design to analyse the effectiveness of the intervention. Quantitative data were analysed using one-way ANOVA and paired sample t-test to assess the effectiveness of the EI. Qualitative data were examined through thematic analysis to explore participants’ experiences and perceptions. Results: Data analyses of the plagiarism test indicated that the experimental group showed significantly greater improvements in referencing skills compared to the control group, with statistical significance at p <.05 for all assessed skills. However, findings for the gathered exercises and assignments demonstrated improvements but not statistically significant in their referencing skills except for paraphrasing. Nonetheless, feedback from focus group interviews indicated positive responses toward EI and its role in enhancing referencing skills.Conclusion: Overall, while EI proved effective in enhancing ESL undergraduates’ referencing skills, there remains room for improvement to fully realize its potential. The study holds a global importance of imparting explicit education on referencing skills, offering educators worldwide a strategic measure aimed at reducing plagiarism act.